2013
DOI: 10.1111/jdv.12286
|View full text |Cite
|
Sign up to set email alerts
|

A study on glabellar wrinkle patterns in Koreans

Abstract: Interpersonal differences in facial animation exist among Koreans. We hope our simple glabellar wrinkles classification enables a more accurate, individualized treatment with botulinum toxin in Asians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 19 publications
0
15
0
7
Order By: Relevance
“…also reference a small number of units in glabellar muscles in Asians compared to Caucasians (8–12 units, 10–30 in women, and 20–40 in men). An explanation would be the higher frequency of the “11” pattern (perpendicular glabellar lines only) and reduced “U” pattern (perpendicular and transverse glabellar lines) among Asians, in addition to the observed differences cited in corrugator muscles . In relation to eyebrows, Asian women are not favored by an abruptly arched brow with a lateral peak because it gives an aggressive look.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…also reference a small number of units in glabellar muscles in Asians compared to Caucasians (8–12 units, 10–30 in women, and 20–40 in men). An explanation would be the higher frequency of the “11” pattern (perpendicular glabellar lines only) and reduced “U” pattern (perpendicular and transverse glabellar lines) among Asians, in addition to the observed differences cited in corrugator muscles . In relation to eyebrows, Asian women are not favored by an abruptly arched brow with a lateral peak because it gives an aggressive look.…”
Section: Discussionmentioning
confidence: 97%
“…Studies in cadavers have shown that the corrugator muscle in Asians is more square, while in Caucasians it is a more extended muscle . Kim et al . also reference a small number of units in glabellar muscles in Asians compared to Caucasians (8–12 units, 10–30 in women, and 20–40 in men).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2–4 Since de Almeida and colleagues 3,4 introduced classification of glabellar contraction patterns, other authors have also attempted to come up with their own classification to tailor to specific ethnic populations. 5 However, such classifications described in literatures focused on Westerners and Koreans, and have not been able to accurately reflect characteristics specific to Chinese.…”
mentioning
confidence: 99%